Enraizamento de miniestacas e qualidade de mudas de Ilex paraguariensis A. St.- Hil. - Pimentel, Nathalia (2020)
Due to the growing commercial interest in non-timber forest products, such as mate leaves (Ilex paraguariensis A. St.-Hil.), mainly in the preparation of drinks and nutraceutical products, the development of clonal propagation techniques for this species is extremely important, and may result in uniform stands and high leaf yield. Given this context, the present study aimed to anatomically characterize the adventitious roots of mini-cuttings and determine the quality of plantlets of mate produced by mini-cuttings. For the anatomical characterization, mini-cuttings of 10SM07, 06SM17, 06SM15 and 06SM12 clones were collected at 0, 30 and 60 days of cultivation in humid chamber, fixed and sectioned on a rotating microtome. Ferric chloride was used to detect phenolic compounds and the lugol solution to identify starch grains. For the study of mini-cutting size, shoots were collected from ministumps maintained in mini-clonal hedge, classified as small (up to 2.5 cm), medium (2.6 to 5.0 cm) and large (5.1 to 10.0 cm) and planted in equal proportions of commercial substrate, vermiculite and sand. At 45, 60, 75 and 90 days of cultivation in humid chamber, mini-cuttings were evaluated for percentages of survival, calogenesis, shooting, number and length of shoot, percentages of rooting, number and length of roots. To evaluate the effect of the substrate compositions, rooted mini-cuttings were cultivated on commercial substrate, subsoil and vermiculite (2:1:1 v/v/v), commercial substrate and subsoil (2:1 v/v) or subsoil, cattle manure and carbonized rice husks (2:1:1 v/v/v). At 30, 60, 90 and 120 days of cultivation, mini-cuttings were evaluated for survival percentage, stem diameter, shoot height, ratio of shoot height and stem diameter and number of leaves. At 120 days of cultivation, three plantlets of each treatment were also evaluated for shoot and root dry mass ratio, total length, surface area, total volume, number of root tips and Dickson quality index. The produced plantlets were randomly distributed in benches with shading screens of 50 and 80% and evaluated for survival percentage, stem diameter, shoot height, and number of leaves at 30, 60, 90 and 120 days of cultivation. The relative content of chlorophyll a, chlorophyll b, total chlorophyll and ratio of chlorophyll a and b were also quantified with the chlorophyll meter. Differences in the rhizogenic capacity of mini-cuttings of four mate clones did not dependend on the presence of anatomical barriers or the accumulation of phenolic compounds, but may be associated with the presence and distribution of starch grains in vegetative propagules. Mini-cuttings with different sizes allowed adventitious rooting, however, the use of small mini-cuttings (up to 2.5 cm) can maximize plantlets production by mini-cuttings. Mate clonal plantlets with satisfactory morphophysiological quality can be produced in commercial substrate and subsoil (2:1 v/v) under 50 and 80% shading.